DI-069 Compliance of adolescents to the treatment of ACNE vulgaris. (14th February 2016) - Csatordai, M; Csoma, ZR; Abraham, R; Bor, A; Soos, G; Doro, P
Abstract : Background: Acne vulgaris affects almost every adolescent to varying extents. Symptoms can range from mild to severe. Symptoms often require medical treatment with local and/or systemic medication. The success of the treatment is greatly influenced by the compliance of the patients. Adolescents often have poor compliance, and it can be challenging for healthcare providers to improve compliance in this special age group of patients. Purpose: The aim of the study was to evaluate compliance of adolescent patients with local and systemic medication for the treatment of acne vulgaris, and to explore the possible causes of non-compliance. Material and methods: Adolescent patients treated for acne vulgaris of varying severity in an outpatient paediatric dermatological department were included in the study. An interview was conducted with the patients, using a structured questionnaire, consisting of 32 questions. Further medical history was taken from the medical records. Results: 213 adolescent patients (122 males and 91 females) were included in the study; mean age was 15.63 ± 2.22 years (mean±SD). Average time between first symptoms occurring and visiting a dermatologist was 1.77 years. A significant number of the patients did not follow the dosing and medicine taking instructions recommended by the doctor. 73.2% applied the local products less frequently and 56.2% took the medicines less often than recommended. In order to attempt to achieve a faster remission, a very small number of them took the medicine more often or applied the local treatment more frequently. Due to side effects, it was necessary to terminate the medication in 9.3% of cases. 42.3% of patients did not return to at least one control visit. 7.6% of patients did not redeem the prescription for financial reasons. Conclusion: Examination and exploration of factors leading to inappropriate patient compliance can provide important help for improving compliance and the development of an efficiently working acne caring system, which in the long run can result in the achievement of more successful treatment. No conflict of interest.